Risk Factors of Corneal Donor Contamination and Post-Keratoplasty Infectious Complication: Poster Presentation - Observational Study - General practitioner - Tania; Monica Matturungan; Lukman Edwar (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Infectious keratitis and endophthalmitis are rare yet devastating complications of corneal transplantation. Some studies have demonstrated increased incidence of infectious post-keratoplasty complications are related to contaminated corneal donor, although its risk factors remain controversial. This study provides concise review on possible risk factors of corneal donor contamination which related to post-keratoplasty infectious complications. Methods : This literature review was conducted by searching PubMed and Proquest for “corneal donor contamination” AND (“infectious complication” OR infection OR endophthalmitis) from the period of 2018-2023. Relevant articles were reviewed and selected for further understanding regarding various risk factors of corneal donor contamination leading to post-keratoplasty infectious complications and its preventive strategies. Results : The rate of corneal contamination varied between studies, ranging from 1,3 to 7,8%. The most common risks of contamination are donor’s diseases (e.g. cardiovascular, cerebrovascular accident) and prolonged time between death and donor retrieval. Longer preservation time (>5 days), environmental situation (temperature and humidity), and prolonged treatment duration on intensive care unit (>4 days) are also considered as its risk factors. Corneoscleral rim culture, addition of antifungal and antibacterial to corneal storage medium, and shortening of corneal processing time should be considered as probable preventive strategies. Conclusion : Donor diseases, prolonged donor retrieval time from death, and longer donor preservation and hospitalization duration, are associated with higher rates of corneal donor contamination. Rapid retrieval and donor handling time, together with corneoscleral rims culture, at least for fungus regarding its better predictive values, should be taken into consideration by corneal donors providing eye banks.